Campina Experimental do Cerrado: an action research at Unesp, Bauru Campus - Enokibara, Marta; Fontes, Maria Solange Gurgel de Castro; Weiser, Veridiana de Lara; Soares, Pedro Henrique Correia; Lima, Fernanda Matos de; Giacomini, Ricardo Marostica (Technical and Scientific Journal Green Cities, 2024)
The aim of this article is to present the planning, design, and execution of the action research project titled "Campina Experimental do Cerrado." This project involves a garden featuring herbaceous and shrub species native to the São Paulo Cerrado and other flowering plants cultivated or naturalized in Brazil. The garden is located in the courtyard of the Central Laboratory of the Faculty of Architecture, Arts, Communication, and Design at São Paulo State University (FAAC-UNESP), Bauru Campus. The Campina involves both undergraduate and graduate students and faculty from the Architecture and Urbanism and Biological Sciences programs. The aim of the project is to gain greater knowledge about the landscaping potential of the tested species to introduce them into landscaping practices and provide support for the implementation of new gardens utilizing native flora, thereby increasing visibility, particularly of the Cerrado biome.
Keywords: Native species; Gardens; Savanna